Distinct classes of cdc2-related genes are differentially expressed during the cell division cycle in plants. - Fobert, P R (1996)
cdc2 and several related genes encode the catalytic subunits of cyclin-dependent kinases, which have been implicated in a number of cellular processes, including control of cell division. As a first step in exploring their function in plants, we isolated four cdc2-related genes from Antirrhinum. Two genes, cdc2a and cdc2b, encode proteins that contain a perfectly conserved PSTAIRE motif characteristic of cdc2 homologs, whereas the products of the two remaining genes, cdc2c and cdc2d, appear to represent a new subclass of proteins that have so far only been identified in plants. Transcripts of these novel genes were localized in isolated cells dispersed throughout actively dividing regions of the inflorescence. This localization is consistent with accumulation that is specific to particular phases of the cell cycle. Correlating cell labeling with nuclear condensation and double-labeling experiments using cdc2 and histone H4 as probes indicated that cdc2c transcripts accumulate during S phase as well as during the G2 and M transition, whereas cdc2d expression was specific to the G2 and M phases. All cells labeled with cdc2d also contained cdc2c label, Indicating that expression of cdc2d completely overlapped with that of cdc2c. Transcripts of cdc2a and cdc2b were detected in all cells within actively dividing regions, but at levels that were only slightly higher than those observed in nondividing areas. These transcripts did not appear to accumulate in a cell cycle-specific fashion. The genes cdc2a and cdc2b were able to partially complement a yeast cdc2 mutation, although all four genes appeared to interfere with the sizing mechanism of yeast cells. We propose that plants contain at least two classes of cdc2-related genes that differ in structure, expression, and perhaps function.